Unique vestiges of Cham civilization - Tran Ky Phuong (Hà Nội : Thế giới, 2000)
This booklet is meant to introduce to you, dear readers who are interested in Unique vestiges of Cham civilization.
Keywords: Vestiges; Cham; Cham civilization -- Tourist